Direct Writing of Metallic Nanoparticle Concentric Multi‐Ring Structures by Template‐Directed Convective Self‐Assembly Processes. Issue 7 (14th April 2014) - Zhai, Shengjie; Jiang, Yingtao; Zhao, Hui; Das, Biswajit
<x xml:space="preserve">Abstract</x> A simple direct writing method using template‐directed convective self‐assembly is employed to fabricate concentric multi‐ring structures of metallic nanoparticles. The concentric ring‐type nanostructures, combined with a gold film, effectively induce a collective surface plasmon resonance, evidenced by a significant enhancement of the fluorescence intensities and Raman signals. This method opens possibilities for many advanced applications, including biosensing and nanophotonics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>